Numerical modelling in investigation of road failure on Malaysian peat soil - Bachok @ Andi Yusoff, Andi Norasyikin (2008)
Road failures are prevalent to common pavement distress, involving cracks and surface deformation, principally when it is constructed on organic soil type. Currently, there is no guideline and specification provided in designing a proper road model associated w i t h this problem. Thus, this matter has lead to get a concerned from Pontian Public W o r k Department in order to find a solution of the problems. This project w i l l focus i n a numerical modelling on a problematic road at Pengkalan Raja Pontian, Section 41, and K M 48 considering cracks and settlement problems of the pavement. It deals with comparison between modelling result and remedial measurement for geotechnical structures. A wide-ranging of field and laboratory testing were conducted to get an input data into the modelling analysis. At survey observation, a full scale of cross section pattern will be reviewed to failure recognizing w i t h the modeling and actual onsite testing. I n conjunction to this matter, the series o f several trials modelling determining the root cause o f the failures and its remedies have been successfully conducted to verify the results. P L A X I S V8.1 software program have been chosen for this analysis related to finite element method. The model complied w i t h actual patterns of the pavement due to failure mechanism, cause(s) o f failures and probable remedies o f failures for future prevention as well.